Domestication of Women in Dettol Soap Commercials - Qorib, Fathul; Saekoko, Aploisari; Setiamandani, Emei Dwinanarhati (Jurnal Komunikasi Nusantara, 2020)
Mass media is one of the most frequently used promotional tools by industry. Unfortunately, advertising not only contains product marketing but also spreads unfair ideas towards women, especially beauty product advertisements. Ramadan Bersih's version from Dettol Soap advertisement depicts a family containing a husband, wife, and children with their respective roles. This study focuses on women's role as housewives in advertisement using gender theory and Roland Barthes' semiotic model. The study found a tendency to place women as housewives responsible for cleaning the house, cooking, supervising children, educating, maintaining children's righteousness, and washing. This study strengthens the previous study's findings regarding women's domestication in advertising. In conclusion, advertising builds a household member's conception role in an unbalanced gender distinction. As a cultural product consumed by the wider community, the industry should pay more attention to advertisements designed to sell goods without eliminating gender education and justice elements